Methods for complex processing and interpretation of radar, acoustic, optical and infrared signals from unmanned aerial vehicles - Карташов, В.М.; Олейников, В.Н.; Рябуха, В.П.; Бабкин, С.И.; Воронин, В.В.; Капуста, А.И.; Селезнев, И.С. (Radiotekhnika, 2020)
Unmanned aerial vehicles (UAVs) are currently widely used in solving a wide range of useful tasks, and on the other hand, they are capable of carrying an active or passive potential threat to various areas of human activity, namely, economic, daily and military. Radar, acoustic, infrared and optical means are currently used to detect and measure the coordinates of unmanned aerial vehicles. Since the areas of capabilities of different methods do not coincide, the prerequisite for the joint use of systems of various types appears to expand the set of measured parameters, the range of observed distances and increase the information content of the obtained data by joint (complex) processing. Complex processing of signals of various information channels can be carried out both at the stage of detection and at the stage of measuring coordinates. Moreover, at the detection stage, it is most in demand due to the complexity of the detection-recognition task. The number of publications in this area is constantly increasing; attention is also paid to complex systems built using various physical sensors. However, the efficiency of functioning of the systems with complex signal processing in practice is not sufficient. The article is devoted to the analysis of the capabilities of integrated systems with the processing of multimodal information obtained from each of the channels used, as well as the development of new more efficient methods for integrating radar, optical, infrared and acoustic channels of integrated systems for the detection and measurement of UAV coordinates.